Meanings attributed by a group of adult men to the experience of having type 2 diabetes mellitus - Gabriela Vanegas; Alejandro Barbosa; Angie Zamora (Interacciones)
Background: Diabetes is a chronic disease that causes various limitations in the personal, family, and social life of the person suffering from it. Aim: It was intended to analyze the meaning attributed by a group of adult men to the experience of having diabetes mellitus type 2. Method: The methodology was qualitative with narrative design. The technique to collect information was a free interview. The group of participants consisted of four adult male parents diagnosed with diabetes mellitus type 2. Intentional sampling was used for the selection. The interviews were recorded in audio and transcribed. An inductive categorical analysis was performed using matrices. There, similarities and differences between participants were identified. Results: Among the findings, it is highlighted that the impact of the disease is presented in the personal, couple, family, and work environment. The main physical consequences are problems of vision, mobility, and insensitivity in lower limbs. On a psychological level feeling of sadness. Conclusions: The family plays a fundamental role in dealing with the disease since it constitutes a source of support in adherence to treatment. It was evident in the children of the participants a construction of meanings around the disease that minimizes its impact. The above has the potential risk for risk behaviors to be repeated in later generations.